Australia - Luhrmann, Baz; Kidman, Nicole, 1967-; Jackman, Hugh (OSCAR : classic movies, 2008)
An English aristocrat who inherits a sprawling ranch reluctantly joins forces with a stock-man in order to protect her new property from a takeover plot.